Comparison between the effects of muscle relaxation and support groups on the anxiety of nursing students: A randomized controlled trial. (November 2016) - Torabizadeh, Camellia; Bostani, Sanaz; Yektatalab, Shahrzad
Abstract: Objective: To compare the effects of the two methods of muscle relaxation and support group on the anxiety levels of the nursing students. Methods: In this randomized controlled trial, 150 nursing students who met the inclusion criteria were divided into three equal groups—muscle relaxation, support group, and control—using the permuted-block randomization method. The experimental groups received 5 sessions of intervention, while the control group did not receive any intervention at all. Using Spielberger's inventory, the researchers measured the anxiety levels of all three groups before and after the intervention. Results: The results showed that both methods had a significant impact on anxiety levels of the nursing students; however, a comparison between their effects revealed that muscle relaxation had been more effective than support group. Conclusions: Considering the seriousness of the issue of anxiety for nursing students, it is important that measures be taken to reduce anxiety in this group. Highlights: All the participants had mild to severe anxiety, which stresses the need for anxiety management. Educators are recommended to apply appropriate methods to reduce students' anxiety. Both muscle relaxation and support group reduced anxiety levels of the students. Muscle relaxation was more effective than support group in reducing anxiety.